Kagedong : Ekspresi Interaksi Teruna Nyoman Dan Daha Di Desa Adat Tenganan Pegringsingan - Ni Ketut Kantriani; Ni Wayan Arini; Gusti Nyoman Mastini (Kamaya: Jurnal Ilmu Agama, 2021)
The cultural diversity found in Indonesia is a proof that Indonesia is a country that is rich in culture on the basis of the form of regional culture that will greatly affect the national culture, and vice versa. Balinese tradition and culture are actually expressions of the interaction of Balinese people with their environment which are divided into two types, namely sekala and niskala. Kagedong, is a form of expression of interaction between nyoman and daha students which gives results about positive norms and endut Masabatan which has a meaning where nyoman and daha students must have a firm resolve in living life. This paper is a qualitative research using ethnographic methods by recording every data obtained from the field that describes, analyzes, and interprets patterns of behavior, beliefs, and shared language from a group of developing cultures.